Tolerance of upland rice cultivars to aluminum and acidic pH - Freitas, Lucas B. de [UNESP]; Fernandes, Dirceu M. [UNESP]; Pivetta, Laercio A.; Maia, Suelen C. M. (Univ Federal Campina Grande, 2016)
Although the upland rice has been known by its moderate tolerance to aluminum, the presence of exchangeable aluminum in acidic soils may inhibit and compromise the adequate plant growth. However, there are few reports detailing modern cultivars used by Brazilian farmers with respect to their susceptibility to aluminum toxicity. This study aimed to characterize the cultivars currently used in the upland rice production with respect to their tolerance to aluminum and their growth under low pH conditions without aluminum. The treatments were arranged in a randomized block design, in a 2 x 9 factorial scheme: presence and absence of aluminum in the nutrient solution and nine upland rice cultivars (BRS Monarca, BRS Pepita, BRS Bonanca, BRS Primavera, BRS Sertaneja, Maravilha, IAC 202, ANCambara and ANa7007), with four replicates. Based on the distribution of upland rice cultivars in quartiles, they were divided into two groups; aluminum-tolerant group: BRS Pepita, BRS Primavera and ANa7007; and aluminum-susceptible group: BRS Monarca, BRS Bonanca, BRS Sertaneja, Maravilha, IAC 202 and ANCambara.
Keywords: Oryza sativa L.; aluminum susceptibility; aluminum resistance